(untitled) (Revista Apotheke, 2021)
The present visual essay is composed by the work entitled “There’s nothing wrong going on” and is in a permanent process of creation. Merging different forms of production, they are graphic and conceptual changes in the Brazilian flag as a form of denunciation and indignation with the current chaotic-political-historical-social period of the country. The new flags in question gain as the streets of Florianópolis (SC) in the form of wheat-paste in a performance action.